Adaptação transcultural da escala Measure of Engagement, Independence and Social Relationships (MEISR™) para a língua portuguesa (Brasil) - Bento, Maiara Medeiros dos Santos (2023)
Introduction: The Measure of Engagement, Independence, and Social Relationships - MEISR™ (Measure of Engagement, Independence and Social Relationships) advocates a family-centered approach and interventions in natural environments, guided by children's routines. It is capable of encompassing children's functional domains in family contexts and home routines to understand their functional participation profile and understand their demands for adjustments and strategies to favor their independence, social relationships and engagement. This scale is officially available in two documents: for the age group 0-3 years and for the age group 3-5 years and is already being used in English, Spanish and Chinese. The scale items are related to the domains and proposals of the International Classification of Functioning, Disability and Health, version for Children and Youth (ICF-CY), a document approved for international use, proposed by the World Health Organization. The ICF-CY contemplates the paradigm shift from the medical model to the biopsychosocial model, considers development as a dynamic process, and shows special attention to family contexts, as it also considers that these enable participation during early childhood, being mediators of great learning opportunities for the child. Thus, the possibility of using a scale with this foundation in Brazil becomes opportune. Objective: Perform the cross-cultural adaptation of the assessment scales: MEISR™ 0 to 3 years and MEISR™ 3 to 5 years, into Brazilian Portuguese. Method: The present study was developed based on the stages of the method proposed by Beaton et al. (2000) referring to cross-cultural adaptation research plus an additional stage proposed by Wild et al. (2005), namely: first stage – Initial Translation of the scale, from Spanish to Brazilian Portuguese by two different translators; second stage – Synthesis: the two translators, together with the mediator, reached a single version of the scale; third stage – Back-translation: translation made from Brazilian Portuguese to Spanish by three translators; fourth stage – Committee of Experts: the Brazilian Portuguese version was analyzed by professionals to verify whether the translated version reflected the same content as the original version in relation to equivalences: semantic, idiomatic, experiential and conceptual, to obtain the pre-production version end of scale; additional stage – Cognitive Breakdown: the pre-final version of the scale was analyzed by people from the general Brazilian population so that they could verify if there was understanding, interpretation and cultural relevance in the texts of the items; fifth stage – Qualitative analysis with the target population: the pre-final version of the scale was applied to the target population; then, the last stage consisted of the analysis of the final report of the cross-cultural adaptation process by the author of the original scale for the approval of the final version. Results: The translation and back-translation stages had divergences, mostly due to the synonym relationship between words and phrases. The suggestions in the Committee of Experts stage and in the Cognitive Deployment stage were analyzed in order to maintain the equivalence of content and there were good levels of agreement. The Qualitative analysis stage with the target population did not present an assessment of little or no understanding, indicating good acceptance by the participants. Finally, all reports and the final version of the cross-culturally adapted MEISR™ scale were approved by the author and his research team. Conclusion: The scales had satisfactory cultural equivalence and resulted in the MEISR™ - Measure of Engagement, Independence and Social Relations, Portuguese language version spoken in Brazil, cross-culturally adapted. Further validity tests may enable the effective use of the Brazilian version scale for clinical and research contexts.